Experimental And Multiscale Finite Element Analysis Of Pultruded Kenaf Composites Under Compressive Impact Load - Seman, Sareh Aiman Hilmi Abu (2019)
Kenaf natural composites are recognized for ecological qualities such as biodegradability, lightweight and renewable. Due to global climate change and greenhouse gas emissions, it has pushed the engagement of kenaf natural composite in load-bearing primary structures. Hence, detailed analysis of structural responses and prediction of damage are needed for structural integrity valuation. In this research project, an extensive experimental and microscopic study were conducted to characterize the mechanical and damage behavior of pultruded kenaf composites at various strain rates using modified compression split Hopkinson pressure bar (SHPB) and universal testing machine (UTM) techniques meanwhile scanning electron microscope (SEM) was used to capture surface morphology of damaged samples. A multi-scale modelling approach which consist of micro, meso and macro-scale models are developed to provide a numerical estimate of the response and failure modes observed in unidirectional kenaf fiber reinforced composites under compressive high strain rate loading. In these models, Hashin-based criteria through a user-defined material subroutine (VUMAT) was used for damage initiation while continuum damage mechanics (CDM) approach was employed to predict the damage progression in composite. Initiation and progression of fiber-matrix debonding was studied by employing cohesive zone elements. The experimental results indicate that the failure stress, failure strain and compressive modulus show different strain rate sensitivity with increasing strain rate. Post-test scanning electron microscopy reveals that the dominant failure modes and mechanisms in the kenaf composites under uniaxial compression are different as the loading condition changes from quasi-static to dynamic. Good correlation with average error of <2% is obtained between the measured experimental and numerically obtained stress-strain curves as well as failure modes which are responsible for damage development and growth. The effect of fibers misalignment and arrangement are also analyzed numerically by considering the overall predicted properties as well as damage areas and pattern which varies due to shear instability and relative distance between fibers. The promising results obtained with these models can be useful in the development of predictive procedures to provide new high strain rate application especially in automotive and aerospace industries for kenaf composite materials.